The Palgrave Handbook of Dark Tourism Studies (Palgrave Macmillan UK, 2018)
This handbook is the definitive reference text for the study of 'dark tourism', the contemporary commodification of death within international visitor economies. Shining a light on dark tourism and visitor sites of death or disaster allows us to better understand issues of global tourism mobilities, tourist experiences, the co-creation of touristic meaning, and 'difficult heritage' processes and practices. Adopting multidisciplinary perspectives from authors representing every continent, the book combines 'real-world' viewpoints from both industry and the media with conceptual underpinning, and offers comprehensive and grounded perspectives of 'heritage that hurts'. The handbook adopts a progressive and thematic approach, including critical accounts of dark tourism history, dark tourism philosophy and theory, dark tourism in society and culture, dark tourism and heritage landscapes, the 'dark tourist' experience, and the business of dark tourism. The Palgrave Handbook of Dark Tourism Studies will appeal to students and scholars with an interest in aspects of memorialisation and morality in sociology, death studies, history, geography, cultural studies, philosophy, psychology, business management, museology and heritage tourism studies, politics, religious studies, and anthropology. .